2022
DOI: 10.1002/essoar.10508190.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of internal tide incoherence : Eulerian versus Lagrangian perspectives

Abstract: The Lagrangian and Eulerian surface current signatures of a low-mode internal tide propagating through a turbulent balanced flow are compared in idealized numerical simulations. Lagrangian and Eulerian total (i.e., coherent plus incoherent) tidal amplitudes are found to be similar. Compared to Eulerian diagnostics, the Lagrangian tidal signal is more incoherent with comparable or smaller incoherence time scales and larger incoherent amplitudes. The larger level of incoherence in Lagrangian data is proposed to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…This is in line with the findings of Zaron and Elipot (2021), which noted that the drifter tidal peaks do not stand out above the background spectrum as strongly as in tide model predictions. Caspar-Cohen et al (2022) consistently demonstrated that the distortion of tidal internal waves induced by surface drifter motions, a process coined as apparent incoherence, leads to broader tidal peaks.…”
Section: Zonally-averaged Spectrum and Kementioning
confidence: 89%
See 3 more Smart Citations
“…This is in line with the findings of Zaron and Elipot (2021), which noted that the drifter tidal peaks do not stand out above the background spectrum as strongly as in tide model predictions. Caspar-Cohen et al (2022) consistently demonstrated that the distortion of tidal internal waves induced by surface drifter motions, a process coined as apparent incoherence, leads to broader tidal peaks.…”
Section: Zonally-averaged Spectrum and Kementioning
confidence: 89%
“…In regions of strong low-frequency flow, the ratio is significantly reduced, with a mean value smaller than 0.4, indicating a substantial underestimation of low-frequency KE from a Lagrangian perspective (Figure 5f). This underestimation results from a larger projection of spatial variability onto temporal one along particle trajectories in energetic regions (LaCasce, 2008;Caspar-Cohen et al, 2022). Indeed, nearby energetic current features, Lagrangian energy thus tends to underestimate Eulerian energy maxima in the core of these features (ratio below 0.5) and overestimate Eulerian energy on the surroundings (ratio above 0.5; Figure 5c).…”
Section: Low-frequency Ke Mapsmentioning
confidence: 98%
See 2 more Smart Citations
“…This suggests that Lagrangian filtering is mostly removing the energy in the SSH field at the tidal and overtidal frequencies. Another possibility is that the transformation to the Lagrangian frame blurs the tidal peaks, spreading their energy over a broad range of frequencies (Caspar-Cohen et al, 2022).…”
Section: Frequency Spectrummentioning
confidence: 99%